Inventarisasi Tumbuhan Akuatik Berpotensi Fitoremediator Air Limbah Industri di Waduk Bunder Gresik - Muhammad Badrut Tamam; Aisyah Hadi Ramadani; Eti Mihatul Maflahah Halma; Chandra Tri Uliana Sari (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
The Bunder Reservoir Ecosystem is composed of various components, both biotic and abiotic. One of the components contained in the reservoir is aquatic plants as phytoremediator for wastewater. The aquatic plant inventory in the Bunder Reservoir aims to determine the diversity of aquatic plant species that have the potential to phytoremediate industrial waste. The research design was descriptive qualitative exploratory. Aquatic plant species were collected using a subjective estimates method with visual techniques. In the waters of the Bunder Reservoir, 17 species of aquatic plants from 13 families were found, including 11 emergent types, 1 free floating, 4 rooted floating, and 1 submersed. Types that have the potential to act as phytoremediators for inorganic waste in the metal categories are A. philoxeroides, A. sessilis, Cyperus sp. Hygrophila sp., I. carnea, I. aquatic, L. perpusilla, N. nucifera, Nymphaea sp., N. indica, P. barbata, and T. latifolia. The aquatic plant that has the potential for phytoremediator of pesticide waste is L. adscenden. While S. sesban tends to remove oil pollutants. Organic waste degrading species consist of T. latifolia, L. perpusilla, I.aquatica, Cyperus sp., And Brachiaria sp